2020
DOI: 10.1038/s41598-020-68699-4
|View full text |Cite
|
Sign up to set email alerts
|

Parametric study on the geometrical parameters of a lab-on-a-chip platform with tilted planar electrodes for continuous dielectrophoretic manipulation of microparticles

Abstract: Advances in lab-on-a-chip (LOC) devices have led to significant improvements in the on-chip manipulation, separation, sorting, and isolation of particles and cells. Among various Loc-based approaches such as inertia-based methods, acoustophoresis, and magnetophoresis, the planarslanted-electrode dielectrophoresis (Dep) method has demonstrated great potential as a label-free, cost-effective, and user-friendly approach. However, the devices built based on this method suffer from low flow throughput compared to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 53 publications
0
19
0
Order By: Relevance
“…( 9)) and the vibration velocities of the substrate (u x and u y are substrate displacement components in eqn. (5) and eqn. ( 6)) is regarded as the interface tangential velocities u a0 and v a0 which can be expressed as 39 ,…”
Section: Limiting Velocity Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…( 9)) and the vibration velocities of the substrate (u x and u y are substrate displacement components in eqn. (5) and eqn. ( 6)) is regarded as the interface tangential velocities u a0 and v a0 which can be expressed as 39 ,…”
Section: Limiting Velocity Methodsmentioning
confidence: 99%
“…Manipulation of microparticles is of utmost importance in a wide array of biomedical, biochemical, and biophysical applications [1][2][3] . Since the emergence of lab-on-a-chip (LoC) technologies, especially in the past two decades, different manipulation strategies, including electrokinetic, hydrodynamic, optical, magnetophoretic, and acoustophoretic based method have been developed [4][5][6][7] . Each method has its portfolio of strengths and weaknesses, which makes them suitable for a particular application.…”
Section: Introductionmentioning
confidence: 99%
“…Microfiltration [4], inertia‐based [5], pinched flow fractionation [6], and deterministic lateral displacement [7] are among the passive methods. Dielectrophoretic [8], acoustophoretic [9], magnetic [10], and optic forces [11] are the most popular active methods used for sorting and separation. The mechanisms, advantages, and disadvantages of each one of these methods are reviewed in detail in the literature [2,12].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have investigated the effect of different geometrical as well as operational parameters on the DEP‐induced displacement of the particles. In our previous study [8], we investigated the effect of the geometry of the electrodes, applied voltage, volumetric throughput, particle size, as well as the height, width, and length of the microchannel on the displacement of the particles. COMSOL Multiphysics simulation results showed that by decreasing the electrode gap and increasing the electrode width to a critical value, which depends on the channel height, the DEP force enhances significantly.…”
Section: Introductionmentioning
confidence: 99%
“…The levitation of cells by n-DEP will decrease the separation effect. Recently, the electrode geometries of slanted electrodes were investigated by the simulation of the induced electric field for the effective and high throughput separation of particles [ 24 ].…”
Section: Introductionmentioning
confidence: 99%